SUN’IY INTELLEKTDAN FOYDALANISH ORQALI 7–8-SINF O‘QUVCHILARINI INGLIZ TILIDA KOMMUNIKATIV KO‘NIKMALARINI SHAKLLANTIRISH. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the development of communicative skills in English among 7th–8th grade students through the use of artificial intelligence technologies. The study examines the influence of AI-based platforms, interactive applications, and digital tools on students’ speaking abilities, listening comprehension, vocabulary acquisition, and communication activity. In addition, the pedagogical potential of artificial intelligence in providing individualized learning, increasing motivation, and creating a real communicative environment is highlighted. The findings demonstrate that the integration of AI technologies into English language teaching enhances educational effectiveness, develops independent thinking skills, and contributes significantly to the formation of communicative competence.